Microglia-Dependent and Independent Brain Cytoprotective Effects of Mycophenolate Mofetil During Neuronal Damage - Kleine, Joshua; Hohmann, Urszula; Hohmann, Tim; Ghadban, Chalid; Schmidt, Miriam; Laabs, Sebastian; Alessandri, Beat; Dehghani, Faramarz (Frontiers in Aging Neuroscience, 2022)
Acute lesions of the central nervous system often lead to permanent limiting deficits. In addition to the initial primary damage, accompanying neuroinflammation is responsible for progression of damage. Mycophenolate mofetil (MMF) as a selective inhibitor of inosine 5-monophosphate dehydrogenase (IMPDH) was shown to modulate the inflammatory response and promote neuronal survival when applied in specific time windows after neuronal injury. The application of brain cytoprotective therapeutics early after neuronal damage is a fundamental requirement for a successful immunomodulation approach. This study was designed to evaluate whether MMF can still mediate brain cytoprotection when applied in predefined short time intervals following CNS injury. Furthermore, the role of microglia and changes in IMPDH2 protein expression were assessed. Organotypic hippocampal slice cultures (OHSC) were used as an in vitro model and excitotoxically lesioned with N-methyl-aspartate (NMDA). Clodronate (Clo) was used to deplete microglia and analyze MMF mediated microglia independent effects. The temporal expression of IMPDH2 was studied in primary glial cell cultures treated with lipopolysaccharide (LPS). In excitotoxically lesioned OHSC a significant brain cytoprotective effect was observed between 8 and 36 h but not within 8 and 24 h after the NMDA damage. MMF mediated effects were mainly microglia dependent at 24, 36, 48 h after injury. However, further targets like astrocytes seem to be involved in protective effects 72 h post-injury. IMPDH2 expression was detected in primary microglia and astrocyte cell cultures. Our data indicate that MMF treatment in OHSC should still be started no later than 8–12 h after injury and should continue at least until 36 h post-injury. Microglia seem to be an essential mediator of the observed brain cytoprotective effects. However, a microglia-independent effect was also found, indicating involvement of astrocytes.